History and Hope in the Heart of Dixie: Scholarship, Activism, and Wayne Flynt in the Modern South. - Foster, Gaines M. (Alabama Review, 2008)
The article reviews the book "History and Hope in the Heart of Dixie: Scholarship, Activism, and Wayne Flynt in the Modern South," edited by Gordon E. Harvey, Richard D. Starnes, and Glenn Feldman.